Identification and characterisation of gut microflora of insectivorous bats from Sarawak - Clarice, M. Asinti (Universiti Malaysia Sarawak (UNIMAS), 2015)
Bats are among the mammalian species that can serve as the host for zoonotic pathogens, like virus, fungi and bacteria. Therefore, it is important to identify and characterise the microbial diversity that reside within these natural host. The purpose of this project is due to the awareness that the natural microflora of insectivorous bats that could potentially cause zoonotic disease to human. The identification and characterisation of the isolated gut microflora were conducted through biochemical tests analysis and molecular methods using PCR for DNA sequence analysis of 16S rRNA. The estimation of viable bacteria present in the gut of 16 bats through rectal swabbing ranged from 1.03xl04 to 1.49xl09 CFU/mL. A total of II genera of bacteria were identified from 97 isolates by using biochemical tests which were Bacillus, Escherichia, Klebsiella, Enterobacter, Acinetobacter Pseudomonas, Staphylococcus, Salmonella, Shigella, Serratia and Vibrio. A total of II species of bacteria from 14 isolates were identified through comparison of the sequences with BLAST, which were Clavibacter michiganensis, Enterococcus faecalis, Acinetobacter calcoaceticlls, A. nosocomialis, A. baumanii, Bacillus thuringiensis. B. cereus, Enterobacter cloacae, E. hormaechei. Staphylococcus scillri. and S. succinlls.